Analisis Prestasi Kerja Terhadap Kinerja Karyawan Badan Pusat Statistik - Riana, Emil Amalia; Darul Fadli, Uus Mohammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this research is to determine the relationship between work performance and employee performance in the workplace environment. Job performance is often considered an important determinant of employee quality and productivity in an organization. Using qualitative methods, data was collected through in-depth interviews with employees of Badab PusatbStatistik Karawang from various company backgrounds. Regression analysis is used to test the hypotheses proposed in this research. It is hoped that the results of this research will provide a deeper understanding of how the performance of Central Statistics Agency employees directly or indirectly contributes to employee performance in different organizational contexts. We also discuss the practical implications of this research for helping employees and organizational leaders effectively improve performance management and employee development.